What does the perfect Companion in Games look like? Development and Validation of the Companion Design Scale - Markus, AndrÃ©; Carolus, Astrid; Wienrich, Carolin (Bina Nusantara University, 2024)
Artificial intelligence gives companions in games (a special form of non-player characters) social, adaptive, and interactive characteristics that can influence the gaming experience. Initial design frameworks for these characteristics have been developed in research, but empirical validation and methods for quantifying their impact on game experience are still lacking. To close this gap, the study developed the Companion Design Scale, which operationalizes the design of companion characteristics and measures their impact on the game experience. Structural equation modeling shows that the scale measures companion characteristics reliably and validly. In addition, the study emphasizes the relevance of companion design in general, but also regarding specific design factors for the game experience. First practical analyses provide design recommendations for game design. This study thus offers insights into the design principles of humanoid AI companions and provides a basis for systematic studies on the psychological effects of artificial companions on users.